2014
DOI: 10.1002/app.41243
|View full text |Cite
|
Sign up to set email alerts
|

High‐temperature resistant superabsorbent based on poly(acrylic acid) with triallylammonium chloride as crosslinking agent

Abstract: A novel high-temperature resistant superabsorbent was prepared by solution polymerization of partially neutralized acrylic acid (AA), using triallylammonium chloride as crosslinker, potassium persulfate as initiator. The factors that influence the waterabsorbing capacity at 25 and 200 C such as mass concentration of monomer, mass ratio of crosslinker to AA, mass ratio of initiator to AA, and neutralization degree were investigated. The structure of the superabsorbent was characterized by Fourier transform infr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…It was revealed that the multiphase hybrid filler was able to preserve as well as showed process synergising effect in polymers and elastomers due to the compatibility and co‐operative interactions at the nanoscale. For example, Hybrid filler systems containing CB and carbon nanotube (CNT) ,CB and nanoclay and CB and nanographene/graphene oxide were developed and the resulting rubber nanocomposites demonstrated remarkable improvement in properties taken for their studies.…”
Section: Introductionmentioning
confidence: 99%
“…It was revealed that the multiphase hybrid filler was able to preserve as well as showed process synergising effect in polymers and elastomers due to the compatibility and co‐operative interactions at the nanoscale. For example, Hybrid filler systems containing CB and carbon nanotube (CNT) ,CB and nanoclay and CB and nanographene/graphene oxide were developed and the resulting rubber nanocomposites demonstrated remarkable improvement in properties taken for their studies.…”
Section: Introductionmentioning
confidence: 99%
“…Combination of CB + carbon nanotube, organoclay + nano‐silica, organoclay + carbon nanotube, CB + Graphene, organoclay + nano‐CaCO 3 , and short jute fibers+ carbon nanotube was also the subject of some studies in rubber–hybrid filler nanocomposites. The synchronous use of CB and nanoclay has been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, these FT-IR peaks suggest the successful development of WR-PPG. Furthermore, small shifts in the FT-IR peaks for NR-PPG as compared to WR-PPG have been noticed possibly due to the reinforcement of the titanium dioxide (TiO 2 ) nanomaterial in the developed polymer matrix of NR-PPG. , …”
Section: Resultsmentioning
confidence: 99%